Microbiological and genetic identification of some probiotics proposed for medical use in 2011. (1st June 2013) - Toscano, Marco; de Vecchi, Elena; Rodighiero, Valentina; Drago, Lorenzo
Abstract : The aim of this work was to evaluate if dietary supplements for medical use available on the Italian and European market in 2011 were correctly labelled in terms of amount of viable bacteria, identity of species or genera and lack of cross contamination by species out of label. Fourteen in twenty-four products (58%) contained all the labelled species in the declared amount and were free of bacterial contamination. Ten in twenty-four products (42%) did not contain the labelled bacterial amount. Moreover, in four of these products (17%), we could not find any viable colony of at least one of the declared species. In two of them the DNA of all missing species could be detected by extracting DNA directly from the product. In conclusion, some products available on the Italian and European market in 2011 were not correctly labelled and did not comply with the specific guidelines.